ANALISIS STUDI KASUS DAN SWOT DI SD NEGERI 3 SANUR - Ida Bagus Gede Surya Abadi; Chindytia; Ni Luh Ayu Rosita Dewi; Umniyati Rizka; Ni Kadek Sinta Lascahya Puji (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of School-Based Management (SBM) at SD Negeri 3 Sanur has generally been carried out fairly well, as evidenced by solid internal governance, a conducive learning environment, and adequate school facilities. Various aspects, including curriculum, student affairs, human resources, finance, and infrastructure management, have been structured effectively to support the learning process. However, public relations management is still sub-optimal, which consequently limits the active involvement of external stakeholders and the school committee. Based on the SWOT analysis, the school's location in Sanur presents a great opportunity to strengthen community cooperation and utilize the local environment as a contextual learning resource. This opportunity must be maximized to address tangible threats, such as intense inter-school competition and ever-increasing demands for educational quality. Therefore, a tactical strategy to enhance school-community communication and collaboration is highly required to support sustainable educational quality improvement.